Influence of hiking trainings on 13 years old adolescents' health - K.V. Mulyk; T.I. Grynova (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of influence of hiking trainings on adolescents' health. Material: the research covered adolescents, who train hiking for one year in hiking circles (20 boys and 16 girls) and adolescents, who do not practice hiking trainings (18 boys and 20 girls). Age of participants was 13 years. The following indices were determined" Ketle -2 index, Robinson's index, indices of Skibinskiy, Shapovalova, Ruffiet. Results: positive influence of hiking trainings on general health condition of adolescents was determined. It has been recommended to practice hiking at days off, summer holidays and during academic year. It was found that general health of group 2 adolescents (who did not practice hiking) corresponds to level below middle (10-13 points). Adolescents of group 1 (who practice hiking) level of general health reaches middle level (14-18 points). Conclusions: it is recommended to assess schoolchildren's health in points. Besides, it is necessary to consider points of every separate index; it will permit to find weak points of adolescents organism's functioning.